Thermal degradation kinetics of a commercial epoxy resin—Comparative analysis of parameter estimation methods. Issue 27 (7th April 2015) - Chairat, Aziza; Joulia, Xavier; Floquet, Pascal; Vergnes, Hugues; Ablitzer, Carine; Fiquet, Olivier; Brothier, Meryl
ABSTRACT The thermal degradation behavior of a commercial epoxy resin, EpoFix® (Struers), has been investigated by thermogravimetry (TG), differential thermal gravimetry (DTG), and differential thermal analysis (DTA) under nonisothermal conditions in an argon atmosphere. Different methods (Kissinger, Flynn–Wall–Ozawa (FWO), Friedman isoconversion methods, and nonlinear least‐squares (NLSQ) estimation method) have been used to analyze the thermal degradation process and determine the apparent kinetic parameters. The methods produce similar results in terms of activation energy estimations. Nevertheless, the NLSQ method has several advantages over the other methods in terms of both characterizing the activation energy and modeling the thermal degradation—i.e., including this model in a resin degradation process simulation. However, it is interesting to combine the NLSQ method with other isoconversion methods: they can reflect the dependence and variability of the activation energies during pyrolysis processes, while providing a good starting point for a nonlinear procedure, especially with respect to the activation energy E. This work is the first step (apparent kinetic reaction) of complete simulation of experimental oven of degradation of epoxy resin coating of impregnate nuclear fuel sample. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42201.